ANGKA KEBERHASILAN POSTEROSAGITTAL ANORECTOPLASTY (PSARP) YANG DINILAI DARI SKOR KLOTZ PADA PASIEN MALFORMASI ANOREKTAL DIBANGSAL BEDAH RSUD ARIFIN ACHMAD PROVINSI RIAU PERIODE JANUARI 2009 – DESEMBER 2014 - Gizka Yolanda Putri; TB Odih Rhomdani Wahid; Huriatul Masdar (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Posterosagittal anorectoplasty (PSARP) is the newest and most widely used technique for the treatment of anorectal malformation (ARM). Standardized assessment of clinical outcome after repairment of ARM can be measured by Klotz score. Klotz score can be used to examine anal function post PSARP. The aims of this research to evaluate the successful rate of PSARP in ARM patients measured by using Klotz score at The Department of Surgery Local State Hospital Arifin Achmad Riau Province. This research was an observational research, using cross sectional design, the population were medical records of ARM patients who had undergone PSARP with colostomy closure in The Department of Surgery Local State Hospital Arifin Achmad Riau Province from January 2009 until December 2013. The result showed the largest age group who performed PSARP was between 4 month-1 years old (58,82%). Among 57,81% were male and 32,35% were female. High lesion in male were found in 67,65% of ARM, whereas intermediet lesion in female were found in 14,70% of ARM. Rectouretra fistula was the most fistula in this research (35,30%). Almost patients in this research got full PSARP as a treatment (85,30%). Minor complication were found in 17,65% and no complications were found in 82,35%. Klotz score post PSARP at this research was categorized as good result 73,53% and best result 17,65%.